Integration Between Stock Market Returns and Interest Rate and its Impact on Inflation : Empirical Evidence from Five Countries - Routh, Bishal (Indian Journal of Research in Capital Markets, 2023)
Purpose : The present study tried to investigate the impact of the equilibrium relationship between deposit interest rates and the stock market return on inflation. Methodology : Five countries, namely Brazil, Hong Kong, India, Japan, and the United States of America, were used as a subject of study. Statistical tools such as Granger and Toda Yamamoto causality were used to understand the causal relationship along with some other auxiliary statistical tools such as Johansen cointegration, t-test, and auxiliary autoregression. For inflation, we used the consumer price index as a proxy, whereas the residual series of purchasing power generated by the deposit interest rate and the stock market return were used as the second series. Findings : We found that for countries where there is no equilibrium relationship, a unidirectional causal relation was established from the residual to the consumer price index, and no causality was found for countries where the relationship existed. The outcome indicated that if the difference in purchasing power generated by two variables has some kind of trend or seasonality, it will cause some sort of movement in the inflation of a nation. Practical Implication : The findings can help in curing economic illnesses, such as deflation and inflation, with proper policy implementation. Originality : The literature consists of mixed results and bidirectional causality; thus, through this paper, I tried to build a narrative to explain the causal direction. Furthermore, I avoided using return or interest for the analysis ; rather, it was converted into purchasing power concerning the base year.